The Role of High-Flow Ventilation in the Treatment of Acute Respiratory Failure - Qoyirov A.Q; Azimov A.A; Boltayev E.B (Genius Journals, 2022)
Prevention, diagnosis and treatment of severe respiratory failure (RF) have been and remain one of the most urgent problems in medicine and resuscitation. Despite the rapid progress in life support methods and respiratory technologies, artificial lung ventilation is not able to adequately and safely prosthetize the function of external respiration. Therefore, the preservation of spontaneous breathing of the patient and the use of auxiliary non-invasive methods of respiratory support in the absence of contraindications seems to be a promising direction in the treatment of ARF , especially in the early stages. In recent years, an innovative respiratory technology has been actively introduced into clinical practice, which makes it possible to non-invasively deliver an air-oxygen mixture to a patient at a high flow rate (up to 60 liters per minute). High flow oxygen therapy (HFOT) provides not only a high flow rate, but also effective humidification and warming of the air-gas mixture with precise control of the oxygen fraction. Various studies have shown that high-flow oxygen therapy appears to be an effective and well-tolerated method of non-invasive respiratory support for respiratory failure of various origins. The purpose of this publication is to review the literature data and preliminary results of our own research on the use of high-flow oxygen therapy in various clinical situations.
Keywords: respiratory failure; respiratory support; non-invasive lung ventilation; high-flow oxygen therapy